Food Insufficiency and Medication Adherence Among People Living with HIV/AIDS in Urban and Peri-Urban Settings - Kalichman, Seth C. (Prev Sci, 2011)
Food insufficiency is associated with medication non-adherence among people living with HIV/AIDS. The current study examines the relationship between hunger and medication adherence in a US urban and peri-urban sample of people living with HIV/AIDS. Men (N=133) and women (N=46) living with HIV/AIDS were recruited using snowball sampling and small media in Atlanta, Georgia. Participants completed computerized behavioral interviews that included measures of demographics, food insufficiency, social support, depression, and substance use, and provided blood specimens to determine HIV viral load. Participants also completed monthly unannounced pill counts to prospectively monitor medication adherence over 8 months. Results indicated that 45% of participants were less than 85% adherent to their medications and that food insufficiency was related to non-adherence; nearly half of non-adherent participants reported recent hunger. Geocoding of participant residences showed that 40% lived more than 5 miles from the city center. Multivariable logistic regression controlling for demographics and common factors associated with adherence showed that the interaction between distance from downtown and experiencing hunger significantly predicted non-adherence over and above all other factors. Medication adherence interventions should address access to food, particularly for people living outside of urban centers.